PENGARUH MEDIA VISUAL OUTDOOR TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI RA HABIBI DESA KUSAU MAKMUR KECAMATAN TAPUNG HULU KAMPAR - Riffi Kurnia Ningsih; Zulkifli Zulkifli; Enda Puspita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based on observations that have been done by researchers on children aged 5-6 years in RA Habibi Kusau Makmur Village Tapung Hulu Kampar sub-distriet still found some problems associated with understanding of the concept of numbers. Such as ; 1). Children’s understanding of the concep of numbers is still limited to mentions numbers, many have not been able to show the numbers of objects.2). Most children have not been able to match the number symbols corresponding to the number of objects. 3). Most childreen also have difficulty in sorting 1-10. 4). The child has not been able to create a saquence of objects 1-10, and 5). Children still find it difficult to make a collections of objects that are equal in number, are not the same and fawer. This research is purposed for to know the influence using outdoor visual media to ability of knowing numbers child concept 5-6 years old in Ra Habibi Kusau Makmur Village Tapung Hulu District Of Kampar.This research is experiment research using one group design. The sample that used is 15 people in this research. File accumulation’s technique that used is observation. Analysis’s file technique t test using SPSS 16.0 program. Hypotheses research is there significant influence to skill knowing numbers child concept after applied outdoor visual media for knowing the hypotheses are refused or accepted based on SPSS 6.0 file can looked t calculate= 27,938 bigger than t table=2,131 (27,938>2,131). As the conclusion Ho refused and Ha accepted that means there are significant difference between before and after doing this experiment with applied outdoor visual media to skill of knowing calculating child concept 5-6 years old. This case can be known for big of influence used outdoor visual media based on calculation using Gain pattern is as big as 82,65% in high categories and as big as 17,35% influenced by another factor.Key Word: Numbers Concept, Outdoor Visual Media.